2018
DOI: 10.2147/cmar.s184781
|View full text |Cite
|
Sign up to set email alerts
|

miR-29a-3p inhibits growth, proliferation, and invasion of papillary thyroid carcinoma by suppressing NF-κB signaling via direct targeting of OTUB2

Abstract: BackgroundAberrant expression of microRNAs (miRNAs) is closely involved in cancer development. Downregulation of miR-29a-3p and its tumor suppressive roles in cancer have been revealed by multiple reporters. However, study of its expression pattern and function in papillary thyroid carcinoma (PTC) is rare.Materials and methodsThe expression of miR-29a-3p in PTC tissues and cells was detected by qPCR. CCK-8, plate clone formation, transwell invasion, Western blot, immunohistochem-istry, and luciferase reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…For example, miR-202-3p was found to be downregulated in PTC tissues, and to repress cell migra- tion as well as invasion in PTC [29]. Furthermore, enforced expression of miR-29a-3p could reduce cell growth, proliferation, and invasion in PTC [30]. Additionally, miR-128 was reported to be associated with the development of PTC and it could suppress the growth of PTC [31].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-202-3p was found to be downregulated in PTC tissues, and to repress cell migra- tion as well as invasion in PTC [29]. Furthermore, enforced expression of miR-29a-3p could reduce cell growth, proliferation, and invasion in PTC [30]. Additionally, miR-128 was reported to be associated with the development of PTC and it could suppress the growth of PTC [31].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-16-5p was reportedly downregulated in breast cancer [76], hepatocellular carcinoma [77] and glioma [78], in agreement with our ndings. Overall, miR-29a-3p has been reported to function as a tumour suppressor and is downregulated in many types of cancers, such as thyroid carcinoma [32], colorectal carcinoma [79] and hepatocellular carcinoma [80].The downregulation of miR-34c-5p has been reported in several types of cancer, such as leukaemia [57] and osteosarcoma [58], and it has been closely associated with poor prognosis. Similarly, miR-490-5p is markedly downregulated in hepatocellular carcinoma tissues [81], in renal cell carcinoma tissues and cells [82] and in childhood neuroblastomas and cell lines [83].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-29a-3p is a potential tumour-suppressive miRNA and is downregulated in several cancer tissues, such as papillary thyroid carcinoma tissues and cell lines [32],hepatocellular carcinoma tissues and cell lines [33], gastric cancer tissues [34] and high-grade glioma tissues [35]. More studies have been conducted on miR-29a-3p than on miR-656-3p, miR-337-5p or miR-655-3p, and studies on exosomederived miR-29a-3p are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Afmid has been reported that they could lead to impaired glucose tolerance in type 2 diabetes [36]. Meanwhile, Otub2 has been shown to act through the inhibition of NF-κB signaling in type 1 diabetes [37,38]. Further experiments should be performed to explore the precise regulatory relationship between these candidate mRNAs and lncRNA TCONS_00230836 as well as PERK/eIF2α-dependent signaling in stearic acid-treated β cells.…”
Section: Discussionmentioning
confidence: 99%